Publisher Correction: Uncovering Sub-Structure and Genomic Profiles in Across-Countries Subpopulations of Angus Cattle (Scientific Reports, (2020), 10, 1, (8770), 10.1038/s41598-020-65565-1) - Cardoso, Diercles Francisco [UNESP] (2020)
In the original version of this Article, Gerardo Alves Fernandes Júnior was incorrectly affiliated with ‘Present address: Centre for Genetic Improvement of Livestock, Department of Animal Biosciences, University of Guelph, Guelph, ON, Canada.’ In addition, an affiliation was omitted for Daiane Cristina Becker Scalez. The correct affiliations are listed below. Gerardo Alves Fernandes Júnior: Department of Animal Science, School of Agricultural and Veterinarian Science, São Paulo State University (UNESP), Jaboticabal, SP, Brazil. Daiane Cristina Becker Scalez: Department of Animal Science, School of Agricultural and Veterinarian Science, São Paulo State University (UNESP), Jaboticabal, SP, Brazil. Present address: Centre for Genetic Improvement of Livestock, Department of Animal Biosciences, University of Guelph, Guelph, ON, Canada. These errors have been corrected in the PDF and HTML versions of the Article.